Harvesting mycorrhizal fungi: does it put Caladenia plants in peril? - Wright, Magali (Universidad de Costa Rica, 2015)
The ‘slice’ method for harvesting mycorrhizal fungi from terrestrial orchids has been suggested for use with endangered species (Dixon 2004, Stewart 2004). It involves uncovering the mycotrophic region (containing mycorrhizal infection) of a plant and removing a slice of tissue for fungal isolation. This method is less destructive than removing whole mycotrophic parts or whole plants, which are the most common published methods of harvesting orchid mycorrhizal fungi.